Perbedaan pengetahuan dan sikap pada siswa siswi melalui edukasi berbasis video dan leaflet tentang HIV/AIDS - Hasnia Hasnia; Endah Purwanti Handayani; Eftyaningrum Dwi Wahyu Astutik; Tiyan Febriyani Lestari; Nasrianti Nasrianti (Holistik Jurnal Kesehatan, 2024)
Background: Reproductive health problems during adolescence such as pregnancy outside of marriage, promiscuity and other problems with all their consequences are one of the reasons why teenagers are at risk of exposure to Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS). Purpose: To analyze differences in knowledge and attitudes among female students through providing video based education and leaflets about HIV/AIDS. Method: Quantitative using quasi-experimental pretest-posttest control group design techniques. The population in this study was 40 students obtained through total sampling techniques. The research was conducted at Santo Yosef Nazaret Vocational School, Jayapura Regency in 2023. The research instrument used a knowledge, attitude and education questionnaire using videos for the intervention group and leaflets for the control group. The data analysis used is univariate analysis presented in the form of a frequency distribution and bivariate analysis using the paired t test and Wilcoxon test. Results: There were differences in the knowledge of female students before and after being given education about HIV/AIDS with a mean pretest score of 13.35 and a posttest of 21.85 in the intervention group and in the control group the mean pretest score was 12.60 and the posttest mean score was 12.60. 20.10 p-value 0.000 (> α=0.05). There were differences in the attitudes of female students before and after being given education about HIV/AIDS with a mean pretest score of 22.85 and a posttest score of 43.95 in the intervention group and in the control group, the mean pretest score was 25.25 and the mean posttest score was 42.65 p-value 0.000 (> α=0.05). Then the results were obtained that there was no significant difference between the provision of video and leaflet based education on knowledge (p=0.2.40) and attitudes (p=606) of female students regarding HIV/AIDS with the value. Conclusion: there was an increase in knowledge and attitudes before and after being given video and leaflet based education so that video/leaflet based education is equally influential in increasing knowledge and attitudes. Suggestion: It is hoped that female students will be more active independently to increase their knowledge about the importance of health problems in adolescents, especially in preventing the transmission of HIV/AIDS, considering the high number of HIV/AIDS cases.   Keywords: Attitudes; HIV/AIDS; Knowledge; Video and Leaflet Based Education.   Pendahuluan: Permasalahan kesehatan reproduksi pada masa remaja seperti kehamilan di luar nikah, pergaulan bebas, dan permasalahan lainnya dengan segala konsekuensi yang menjadi salah satu penyebab remaja berisiko terpapar Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS). Tujuan: Untuk menganalisis perbedaan pengetahuan dan sikap pada siswa siswi melalui pemberian edukasi berbasis video dan leaflet tentang HIV/AIDS. Metode: Kuantitatif dengan teknik quasi experimental pretest-posttest control group design. Populasi dalam penelitian ini sebanyak 40 siswa didapatkan melalui teknik total sampling. Penelitian dilakukan di SMKS Santo Yosef Nazaret Kabupaten Jayapura pada Tahun 2023. Instrumen penelitian menggunakan kuesioner pengetahuan, sikap, dan edukasi menggunakan video untuk kelompok intervensi dan leaflet untuk kelompok kontrol. Analisis data yang digunakan adalah analisis univariat yang disajikan dalam bentuk distribusi frekuensi dan analisa bivariat menggunakan uji t berpasangan dan uji Wilcoxon. Hasil: Ada perbedaan pengetahuan siswa siswi sebelum dan sesudah diberikan edukasi tentang HIV/AIDS dengan nilai pre-test mean 13.35 dan post-test 21.85 pada kelompok intervensi dan kelompok kontrol didapatkan nilai pre-test mean sebesar 12.60 dan nilai post-test mean sebesar 20;10  p-value 0.000 (> α=0.05). Ada perbedaan sikap siswa siswi sebelum dan sesudah diberikan edukasi tentang HIV/AIDS dengan nilai pre-test mean 22.85 dan post-test 43.95 pada kelompok intervensi dan kelompok kontrol didapatkan nilai pre-test mean sebesar 25.25 dan nilai post-test mean sebesar 42.65 p-value 0.000 (> α=0.05). Kemudian diperoleh hasil bahwa tidak terdapat perbedaan yang signifikan antara pemberian edukasi berbasis video dan leaflet terhadap pengetahuan (p=0.2.40) dan sikap (p=606) siswa siswi tentang HIV/AIDS dengan nilai. Simpulan: Terjadi peningkatan pengetahuan dan sikap sebelum dan sesudah diberikan edukasi berbasis video dan leaflet, sehingga edukasi berbasis video dan leaflet sama-sama berpengaruh dalam meningkatkan pengetahuan dan sikap. Saran: Diharapkan kepada siswa siswi agar lebih aktif secara mandiri untuk menambah pengetahuan tentang pentingnya masalah kesehatan pada remaja khususnya dalam mencegah penularan HIV/AIDS, mengingat tingginya angka kasus HIV/AIDS.   Kata Kunci: Edukasi Berbasis Video dan Leaflet; HIV/AIDS; Pengetahuan; Sikap.